2021
DOI: 10.1016/j.mvr.2020.104093
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α requires Ezrin to regulate the cytoskeleton and cause pulmonary microvascular endothelial barrier damage

Abstract: Acute respiratory distress syndrome (ARDS) is a rapidly progressive disease with unknown pathogenesis. Damage of pulmonary microvascular endothelial cells (PMVECs) caused by inflammatory storm caused by cytokines such as TNF-α is the potential pathogenesis of ARDS. In this study, we examined the role of ezrin and Rac1 in TNF-α-related pathways, which regulates the permeability of PMVECs. Primary rat pulmonary microvascular endothelial cells (RPMVECs) were isolated and cultured. RPMVECs were treated with rat TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…As a result, a similar trend to that in our previous observations stimulated by 100 ng/ml TNF-α was observed (Tang et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As a result, a similar trend to that in our previous observations stimulated by 100 ng/ml TNF-α was observed (Tang et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we systematically investigated the role of Ezrin protein on endothelial permeability in TNF-α-stimulated PMVECs. Moreover, FAK, RhoA, or their combination was considered as the required signal mechanism, which differed from the previous works (Koss et al, 2006;Shao et al, 2013;Fei et al, 2019;Tang et al, 2021). The process can be demonstrated as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALI and its severe form, ARDS, are potentially fatal complications of sepsis and important causes of high mortality in critically ill patients [21]. Several recent studies have linked ERM to LPS-induced lung injury [4][5][6]. However, the speci c role of ezrin during this process has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Ezrin/radixin/moesin proteins (ERMs) are members of the protein 4.1 superfamily and function as linkers that connect the actin cytoskeleton to the plasma membrane of cells [3]. Recent studies have reported that ERM phosphorylation results in the loss of endothelial barrier integrity, thus leading to lung in ammation [4,5]. Another research involving an LPS-induced ALI model showed that the introduction of a phospho-null moesin mutant into the mouse lung signi cantly attenuated LPSinduced lung in ammation and vascular leakage, thus suggesting that moesin dephosphorylation protects against lung injury [6].…”
Section: Introductionmentioning
confidence: 99%